Influence of the Preparation Methods on LiFePO4-Li3V2(PO4)3 Hybrid Material - Xiao-Dong, Guo; Ben-He, Zhong; Hong, Tang; Yan, Tang; Yan-Jun, Zhog; Yang, Song (Asian Journal of Chemistry, 2011)
The "lithium iron(II) phosphate"-"lithium vanadium phosphate" hybrid composites (LFVP) were synthesized by two different methods, chemical blending and physical blending. The materials obtained from the experiment were samples of chemical LFVP (C-LFVP) and physical LFVP (P-LFVP). Comparing with the lithium iron(II) phosphate (LFP) and lithium vanadium phosphate (LVP), both hybrid samples showed improvements in electrochemical performance. The new substances yielding in the blending process were largely accountable for the improvements. Compared to P-LFVP sample synthesized by physical blending, the C-LFVP sample synthesized by chemical blending had demonstrated uniform shape, smooth surface and superior electrochemical performance. Thus, preparation methods had substantial influences on the hybrid materials. In the physical blending process (ball milling), the mechanical energy (high-speed ball running) undermined the crystallinity and grain morphology of the P-LFVP. The electrochemical performance of the chemical C-LFVP was much better than that of P-LFVP. The discharge capacity of C-LFVP is 192 mA h g-1 at 0.1 ºC, which was significantly higher than that of P-LFVP at the same rate. So chemical blending was a preferred method to prepare LFVP hybrid materials.